2010
DOI: 10.2460/javma.237.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colostral volume, interval between calving and first milking, and photoperiod on colostral IgG concentrations in dairy cows

Abstract: Dairy producers should harvest colostrum as soon as possible after calving to optimize transfer of passive immunity in neonatal calves. Photoperiod can be manipulated without adversely affecting colostral IgG concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
1
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 30 publications
10
75
1
17
Order By: Relevance
“…Time interval between calving to milking In agreement with previous international studies (Lomba et al, 1978;Straub and Matthaeus, 1978;Moore et al, 2005;Morin et al, 2010), colostrum IgG concentration was negatively associated with the interval from calving to colostrum collection. Corroborating the results from Straub and Matthaeus (1978), the present study failed to identify a significant difference in IgG concentration for cows milked up to 9 h post-calving, although IgG decreased thereafter.…”
Section: Colostral Weightsupporting
confidence: 91%
See 4 more Smart Citations
“…Time interval between calving to milking In agreement with previous international studies (Lomba et al, 1978;Straub and Matthaeus, 1978;Moore et al, 2005;Morin et al, 2010), colostrum IgG concentration was negatively associated with the interval from calving to colostrum collection. Corroborating the results from Straub and Matthaeus (1978), the present study failed to identify a significant difference in IgG concentration for cows milked up to 9 h post-calving, although IgG decreased thereafter.…”
Section: Colostral Weightsupporting
confidence: 91%
“…Possible reasons for the relatively high mean IgG concentration of colostrum in the present study include a short calving to colostrum collection interval (Morin et al, 2010), good grass-based nutritional management, and the use of a relatively low-yielding cow type that produces low weight of colostrum. The average total lactation milk yield for the cows in the present study was 5256 kg, considerably lower than yields reported in previous studies; Pritchett et al (1991) reported mean total lactation milk yield of 9079 kg.…”
Section: Colostral Qualitymentioning
confidence: 86%
See 3 more Smart Citations